Language and the Law Global Perspectives in Forensic Linguistics from Africa and Beyond. - Ralarala, Monwabisi K. (Studies in Forensic and Legal Linguistics in Africa and Beyond (SF&LLA) Ser., 2022)
My familiarity with Professor Yusef Waghid's scholarship and our collaborationspan more than two decades. Therefore, a few words cannot appropriatelyencompass my account of the magnitude of his academic profile coupled withhis personal qualities and engagement.